Anti-Müllerian hormone a surrogate of follicular fluid oxidative stress in polycystic ovary syndrome? - Vale-Fernandes, Emídio; Moreira, Mafalda V.; Rodrigues, Bárbara; Pereira, Sofia S.; Leal, Carla; Barreiro, Márcia; Tomé, António; Monteiro, Mariana P. (Frontiers in Cell and Developmental Biology, 2024)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women at childbearing age. Anti-Müllerian hormone (AMH) is a widely accepted sensitive marker of ovarian reserve, which has been suggested that could also act as biomarker of ovarian morphology for PCOS diagnosis. Oxidative stress (OS) is known to be associated and have a negative impact factor in several reproductive conditions, including PCOS. However, the relationship between circulating AMH and OS within the follicular fluid (FF), and its potential impact on in vitro fertilization (IVF) outcomes of women with PCOS, remains largely unexplored. A total of 84 women, with PCOS (n=30) or ovulatory controls (n=54), were enrolled in this study. Women underwent individualized controlled ovarian stimulation for oocyte retrieval. Blood and FF obtained from mature follicles were collected at the time of oocyte retrieval, for measuring total testosterone, ∆4-androstenedione, progesterone, sex hormone binding globulin (SHBG) and AMH. OS in the FF was assessed by measuring total antioxidant capacity (TAC) through the ferric reducing antioxidant power (FRAP) and lipid peroxidation (LPO) by quantification of malondialdehyde (MDA) levels. Our results demonstrated that women with PCOS had significantly higher plasma levels of AMH, ∆4-androstenedione, total testosterone and a free androgen index (FAI) than observed in non-PCOS controls. In women with PCOS, total testosterone and AMH levels in the FF were also higher, while TAC was lower compared to non PCOS. Furthermore, circulating AMH levels were positively correlated with ∆4androstenedione, albeit negatively correlated with TAC. In this study we demonstrated that the susceptibility to OS, as assessed by the total antioxidant capacity in the FF, is higher in women with PCOS and inversely related to AMH levels. This study results lead us to forge the reasonable hypothesis that the greater susceptibility to OS within the follicle microenvironment is potentially at the end of a roadway that starts with elevated ∆4-androstenedione and AMH within the FF, which in turn are mirrored by circulating AMH and androgen levels. Thus, suggesting that circulating AMH levels could act as a surrogate biomarker of follicular fluid oxidative stress in women with PCOS.